Consumer Preference Survey of De Choice Fast Food in Uyo Metropolis, Akwa Ibom State, Nigeria - Mfon and Imoh Uford, Abasiama (British Journal of Marketing Studies, 2022)
The purpose of this study was to provide a description of fast-food consumers, analyze their preferences, determine the adequacy of current packaging material, and recommend improvements in media vehicles and promotional strategy. A sample of 172 consumers entering De Choice Fast Food in Uyo Metropolis, were conveniently selected, while descriptive statistics was used in analyzing the data obtained. Findings showed that De Choice Fast Food consumers were predominantly resident in Uyo metropolis, singles, more males than females with some levels of education, relatively young people with average incomes. Of all the consumers, those who liked De Choice Fast Food products thought it was tasty, with great value while those who had complaints said their price was on the high side but that the foods/snacks were spicy. Furthermore, the findings showed that consumers prefer white transparent clear plastic packaging to other materials and that they consider De Choice Fast Food location, parking space and interior to be adequate. More so, they love a variety of music like gospels, pop, rock and traditional music and are mostly reached through De Choice bill boards. From these findings, we concluded that most of the consumers of De Choice Fast Food products were average income earners, quite young and enterprising men and women; the foods were of good taste and great value and billboards were the most effective means of reaching most of the consumers. Based on this, we recommended that a complete repackaging of their service strategy be revisited through process engineering of key service areas.  Citation: Abasiama Mfon and Imoh Uford (2022) Consumer Preference Survey of De Choice Fast Food in Uyo Metropolis, Akwa Ibom State, Nigeria, British Journal of Marketing Studies, Vol. 10, Issue 2, pp.13-34